Hubungan usia ibu dan jarak kehamilah dengan kejadian persalinan preterm - Nurmila Nurmila; Yuni Kusmiyati; Hesty Widyasih (Jurnal Kesehatan Ibu dan Anak, 2012)
According to the data of WHO in 2012, Indonesia in 2010 was the fifth ranked of 1O nation, with the highest preterm birth rate in the world. The morbidity and mortality of mother and infant in Indonesia was increased because of the risk factors. three 'late' and four 'too' were excessive handlings. One of the risk factors was maternal age and pregnancy interval. The study was performed in the Regional Public Hospital of Wates, Province of Special Region of Yogyakarta. This study was case -control study using bivariate and multivariate analyses. ln getting samples, this study used the method of purposive sampling with the inclusion1nd exclusion coteries and it was obtained 80 preterm births used as casual groups and 80 aterm births used as controlling groups. Based on the chi-square analysis, there was a relationship between maternal age and the incidence of preterm birth (p-value:0.013; CI: 95%), and there was a relationship between interval pregnancy and the incidence of preterm birth (p-value: 0.00; Cl:95yo). The characteristic of intermediate education of preterm birth was 51 .3%, the unemployment subjects to bear an preterm infant was 76.3%, the unrisk parities to bear preterm infant was 51 .30%, the unrisk age to bear an aterm infant was 75%, the unrisk interval pregnancy to bear an aterm infant was 92.5%, The multivariate analysis of age groups found the risk of preterm birth (OR: 3.30; CI: 95%), and interval pregnancy had the risk of preterm biRTh (OR:9.24;Cl:95%). In the regression test of logistic probability, it found that the probability of preterm birth was 43%.